2004
DOI: 10.1292/jvms.66.847
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive Disorders in Pubertal and Adult Phase of the Male Rats Exposed to Vinclozolin during Puberty

Abstract: ABSTRACT. Vinclozolin (VCZ) is a systemic dicarboximide fungicide with antiandrogenic activity. Reproductive toxicity of VCZ was investigated in male rats exposed to VCZ during puberty. Sprague-Dawley male rats aged with 35 days were assigned to six different groups; negative control, positive control receiving flutamide (100 mg/kg), VCZ (100, 200 and 400 mg/kg), and a combination of VCZ (200 mg/kg) + methyltestosterone (100 mg/kg). The animals were treated with test compounds by oral gavage daily during 35 to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
1
1

Year Published

2005
2005
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 12 publications
1
15
1
1
Order By: Relevance
“…This action of MP partly is in consensus with that of flutamide or vinclozolin, in which testosterone level increased due to suppression of feed-back inhibition of androgens on the anterior pituitary (O'Connor et al, 1998). The suppression of feedback inhibition may secondarily increase the LH secretion and a blockade of Leydig cell androgen receptors, leading to increased secretion of testosterone (Andrews et al, 2001;Yu et al, 2004). However, in the present study, the LH level was also decreased in the treated testis, indicating a direct effect on the anterior pituitary.…”
Section: Hormone Estimation In the Testissupporting
confidence: 52%
See 1 more Smart Citation
“…This action of MP partly is in consensus with that of flutamide or vinclozolin, in which testosterone level increased due to suppression of feed-back inhibition of androgens on the anterior pituitary (O'Connor et al, 1998). The suppression of feedback inhibition may secondarily increase the LH secretion and a blockade of Leydig cell androgen receptors, leading to increased secretion of testosterone (Andrews et al, 2001;Yu et al, 2004). However, in the present study, the LH level was also decreased in the treated testis, indicating a direct effect on the anterior pituitary.…”
Section: Hormone Estimation In the Testissupporting
confidence: 52%
“…In the present study also, Leydig cells maintained normal structure, although testosterone level increased. In general, antiandrogens induce structural changes in the testis, characterized by hypertrophy of Leydig cells (Andrews et al, 2001;Yu et al, 2004). In the present study, changes in the testicular structure were observed, although Leydig cells were normal, thus making a difference with a typical anti-androgen.…”
Section: Histopathological Changes In the Testis 1 Qualitative Changescontrasting
confidence: 42%
“…Since vinclozolin effects are driven through AR antagonism, it is not surprising that there are no reported associations between this compound and prostate cancer, an androgen-dependent disease. Exposure of rats to vinclozolin during development results in reduced prostate gland growth and size which would be expected for an anti-androgen (Yu et al 2004). Of interest, however, are recent studies with maternal (i.e.…”
Section: Vinclozolinmentioning
confidence: 99%
“…Fungicides are by far the most employed but there are important disparities of practices among the French wineyielding regions (Ambiaud 2012). For example, vinclozolin is well known for its action on male fertility (Yu et al 2004), even at early low-dose exposure (Eustache et al 2009, Auger et al 2010. This peculiar fungicide product, acting as an anti-androgen, was widely used in grapevine, fruit, and vegetable cultures from 1978 to 2007 in France, and is also increasingly suspected to have transgenerational effects (Auger et al 2013, Skinner et al 2013.…”
mentioning
confidence: 99%